The effectiveness of targeted therapy of various genetically engineered biological drugs in the treatment of bronchial asthma - Madina S. Shogenova; Svetlana H. Hutueva; Laura S. Shogenova (Терапевтический архив, 2024)
This article presents the experience of successfully switching therapy from omalizumab 150 mg to benralizumab 30 mg/1 ml in a patient with a combined allergic and eosinophilic phenotype in the presence of hypersensitivity to nonsteroidal anti-inflammatory drugs. The effectiveness of biological therapy was evaluated when switching from omalizumab 150 mg subcutaneously at a dose of 600 mg for 36 weeks. Therapy for the drug benralizumab 30 mg/1 ml subcutaneously the first three injections monthly, the rest a month later for 52 weeks with bronchial asthma (BA), a severe uncontrolled course with a combined allergic and eosinophilic phenotype in the presence of hypersensitivity to nonsteroidal anti-inflammatory drugs in a patient Ch., born in 2004. Switching therapy from omalizumab 150 mg to benralizumab 30 mg/1 ml allowed to achieve complete control of asthma symptoms (AST = 23 points), to achieve the absence of asthma exacerbations during 52 weeks, restore respiratory function to normal values, as well as improve the quality of life. The study reflects the good tolerability, high efficacy and safety of biological therapy when switching from one genetically engineered biological drug (GIBP) omalizumab 150 mg to another GIBP benralizumab 30 mg/1 ml in severe uncontrolled asthma with a combined allergic and eosinophilic phenotype in the presence of hypersensitivity to nonsteroidal anti-inflammatory drugs. Therapy with benralizumab 30 mg/1 ml in severe BA has demonstrated a more effective clinically significant improvement in the course of the disease, control of symptoms of the disease. Reduction of exacerbations, normalization of respiratory function indicators, complete control of the disease has been achieved. Consequently, the use of different biological molecules for the therapy of BA with a combined allergic and eosinophilic phenotype contributes to achieving disease control, improving the patient's quality of life and reducing the dose of oral glucocorticosteroids. The targeted biological drug benralizumab 30 mg/1 ml has a targeted effect on the key links in the pathogenesis of severe uncontrolled asthma with a combined allergic and eosinophilic phenotype in the presence of hypersensitivity to nonsteroidal anti-inflammatory drugs and reduces the burden of severe disease.